Tazkiyah al-Nafs wa ‘Alāqatuhā bi al-Sa’ādah ‘inda Ibn Qayyim al-Jawziyyah - Nur Hadi Ihsan; Munir Munir; Dedy Irawan (Universitas Darussalam Gontor, 2021)
Abstract This paper tries to explore the concept of purification of the soul (tazkiyat al-nafs) and its relationship to happiness according to Ibn Qayyim al-Jauziyyah. Ibn Qayyim explained that the soul (nafs) is the essence of man with the ability to incline to good or evil. The soul was created with flaws and imperfect, but it will become perfect with the purification (tazkiyatun nafs). This research is a library study and the data collected using documentary techniques. The collected data were analyzed utilizing analytical-descriptive method. This study concludes the following. First, the purification of the soul according to Ibn Qayyim is not only to purify the human soul, but also to purify his faith. Second, Ibn Qayyim's method of purifying the soul is by takhalli (emptying the soul) from all impurities of sin and tahalli (filling the soul) with obedience to Allah in the form of the main practices to achieve soul perfection. Third, happiness according to Ibn Qayyim is the happiness of the spiritual heart (nafs) as well as the happiness of useful knowledge. The highest and greatest happiness is the happiness of the heart in achieving ma'rifatullah. Fourth, the relationship of purification of the soul with happiness according to Ibn Qayyim is like a mirror in which there is a law of causality (cause and effect). The more the mirror of the heart is cleansed of the rust of sin, the image of His Throne will be clearer and more visible, so that it leads to ma'rifatullah. Abstrak Tulisan ini mencoba mengungkap konsep penyucian jiwa (tazkiyat al-nafs) dan hubungannya dengan kebahagiaan menurut Ibnu Qayyim al-Jauziyyah. Ibnu Qayyim menjelaskan bahwa Jiwa (nafs) adalah esensi manusia, ia memiliki kemampuan untuk condong kepada kebaikan atau kejahatan. Oleh karena itu, jelas sekali bahwa jiwa itu diciptakan dengan kekurangan dan tidak sempurna, ia akan menjadi sempurna dengan penyucian jiwa. Penellitian ini adalah studi kepustakaan dan untuk mengumpulkan data digunakan teknik dokumenter. Data yang terkumpul dianalisis dengan metode deskriptif-analitik. Kajian ini menyimpulkan empat temuan berikut. Pertama, penyucian jiwa menurut Ibnu Qayyim bukan hanya untuk menyucikan jiwa manusia, tetapi juga menyucikan akidahnya, karena syirik merupakan najis dan kotoran. Kedua, metode Ibnu Qayyim dalam penyucian jiwa adalah dengan takhalli (pengosongan jiwa) dari segala kotoran dosa dan tahalli (pengisian jiwa) dengan ketaatan kepada Allah berupa amalan-amalan utama untuk mencapai kesempurnaan jiwa. Ketiga, kebahagiaan menurut Ibnu Qayyim adalah kebahagiaan hati spiritual (nafs) seperti halnya kebahagiaan ilmu yang bermanfaat. Kebahagiaan tertinggi dan terbesarnya adalah kebahagiaan hati dalam mencapai ma’rifatullah. Keempat, hubungan penyucian jiwa dengan kebahagiaan menurut Ibnu Qayyim ibarat cermin yang di dalamnya terdapat hukum kausalitas (sebab akibat), semakin cermin hati dibersihkan dari kotoran karat dosa maka gambar Arsy-Nya akan semakin jelas dan tampak, sehingga mengantarkan kepada ma’rifatullah.